Testing of high heat flux 3D printed aluminium evaporators - Gerner, H.J. van; Smit, M. de; Helvoort, D. van; Es, J. van (My University, 2018)
The amount of waste heat that is generated in electronic components in aerospace application is increasing because of higher electrical power demands. As a result, conventional cooling methods are not able to maintain the electronic component below its maximum temperature. For this reason, a two-phase Mechanically Pumped Fluid Loop is being developed for high-power electronic components in a commercial aerospace application. These electronic components generate a heat load of 722 W on a 3.8 cm x 3.8 cm surface, resulting in a heat flux of 50 W/cm2. Tests with 8 different evaporator samples were carried out to determine the heat transfer coefficients and pressure drop and to select the optimal evaporator sample that is further developed in the detail design phase of the project. The tests show that the 3D printed aluminium evaporators are able to keep the heat source well below its maximum temperature.